TDOA/AOA-Based Unknown Surveillance Radar Localization Scheme Using a Single UAV - Jeong, Wooseong; Lim, Jaesung; Baek, Hoki; Koo, Jayeul (Journal of Korean Institute of Communications and Information Sciences, 2022)
When UAV is used as a sensor node for radar signal detection to estimate the location of the enemy surveillance radar, there are various advantages such as rapid node operation. In particular, in the case of using a single UAV, it is possible to drastically reduce operating costs and free from the problem of time synchronization among multiple UAVs. The technique recently proposed for estimating unknown surveillance radar position using a single UAV employs TDOA, making it difficult to obtain outstanding Dilution of Precision(DOP) and also difficult to approach radars located in enemy lines. Therefore, this paper proposes a combination of TDOA/AOA that estimates the arrival time difference and arrival angle of the radar pulse signal from the beam rotation information of the monitoring radar and the pulse repetition interval to determine the location. The proposed technique was evaluated through MATLAB simulation that compared to the TDOA technique, it could mitigate the DOP dependencies arising from the position estimation of unknown radars and significantly improve the position estimation accuracy. In particular, it was confirmed that if the radius of rotation of a single UAV is guaranteed more than a certain level, it has high accuracy regardless of rotation size.
Keywords: DOP; Position estimation; Surveillance radar; TDOA/AOA; UAV